التأثيرات الأولية لبعض المستخلصات النباتية على الاكاروس الأحمر ذي البقعتين Tetranychus urticae koch(Acari: Tetranychidae) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
بحثاً عن مصادر طبيعية لمركبات آمنة تتجاوز سلبيات المبيدات الكيميائية التقليدية من تسممات للأحياء غير المستهدفة وتلوث للبيئة،نفذت تجارب مخبرية لتحديد التأثيرات الأولية للمستخلصات المائية لأنواع نباتية من فصائل مختلفة في الساحل السوري ،وذلك على إناث الطور البالغ للأكاروس Tetranychus urticae Koch. أظهرت النتائج من خلال معاملة الشرائح الورقية (leaf disk) لنبات الفاصولياء العادية (Phaseolus vulgaris L.) بمستخلصات النباتات المدروسة، إمتلاك عشرة أنواع منها لفعالية بيولوجية جيدة على الصفات الحيوية للإناث المعاملة/ كما أثبتت إحداث تأثيرات متعددة على الأنظمة الحيوية للإناث،ومنها التأثير القاتل الذي حسبت درجته وفقاً لمعادلة Abbott. متوسط نسبة الموت تراوحت بين  56.87%  مع مستخلص قثاء الحمار و100%  مع بذور المشمش عند المعاملة بنسبة 1:1،وقد تراجعت عموماً درجة الفعالية مع الزيادة في معدل تخفيف المستخلصات. أحدثت مستخلصات الأزدرخت،قثاء الحمار،السمالكس والهواء الخشن تأثيراً طارداً على الأفراد. لوحظ حصول تأثيرات مانعة للتغذية بعد المعاملة بمستخلصات قثاء الحمار،الديس الإفرنجي، الترمس الأزدرخت والسمالكس . ثبت بالتحليل الإحصائي وجود فروق معنوية بين الأنواع المختبرة من جهة والتخفيفات المستخدمة مقارنة مع المستخلص الأساسي من جهة ثانية. أظهرت النتائج إمتلاك مستخلصات أنواع عديدة لفعالية بيولوجية جيدة على الصفات الحيوية للأكاروسات الضارة بالمزروعات والتي تبشر بإمكانية العثور على مواد فعالة إضافية من مصادر طبيعية وإيجاد مركبات مشابهة وذلك في حال التعمق بدراسة طبيعة تلك المستخلصات وتحديد نوع المركبات التي تحتويها. In order to search for safe natural compounds that have less negative effects on non-target organisms and environment pollution than the traditional chemical pesticides, we did laboratorical bioassys to ditermine the preliminary effects of equatic extracts of group plant species which grow in the Syrian coast region belonging to different families . Treatments were carried out on two female adults spotted spider mite (Tetranychus urticea Koch) . Treating leaf disks of common beans (phaseolus vulgaris L.) with the studied plants extracts showed that there were ten plants that had good biological efficiency on the bioproperties of treated individuals. Results proved multiple effects on the females biological properties as lethal effect which calculated according to Abbott equation . - Mortality ratio means ranged between 56.87% by using E.elaterium extract and 100% by using P.armeniaca seeds extract when ratio 1:1 was used. but it decreased when we diluted the extracts some plants extracts caused repellant effect as M. azedarach, E. elaterium. S. aspera and. Asparagus SP. We observed antifeedant effect when treating with extracts E. elaterium  .L. camara,  L. termis, M.azedarach and  S.aspera. Statistical analyses showed high differences between laboratorical kinds on one hand and dilution used compared with the main abstracts the other hand . Our study showed good activity of many plant species extracts on the bio-properties of acarids which damage crops. that gives hope to find additative active ingreadient from natural sources and manufacturing similar compounds artificialy if the extracts compounds are difined carefully .